Central Andean (28–34°S) flood record 0–25 ka from Salinas del Bebedero, Argentina. (September 2022) - Quade, Jay; Dente, Elad; Cartwright, Alyson; Hudson, Adam; Jimenez-Rodriguez, Sebastian; McGee, David
Abstract: The Salinas del Bebedero occupies an isolated basin in the foreland of central Argentina at 33°S and was flooded repeatedly over past 25 ka. Isotopic evidence demonstrates that this flooding was due to overflow of the nearby Río Desaguadero with waters derived from the distant (≥300 km) central Andes between 28–34°S. Stratigraphic and shoreline evidence shows that floods occurred most frequently from 14.3 to 11.4 ka, followed by lesser events between 14.3 to 11.4 ka, and during the late Holocene from 2.6 to ca. 0.2 ka. Hydraulic modeling (2D HEC-RAS) shows that these floods could have originated from repeated subglacial drainage or sudden outbursts with a volume of >100 × 10 6 m 3 and a peak discharge of >1, 000 m 3 s -1 each. The absence of flood deposits from 11 to 3 ka points to exceptionally dry and virtually ice-free conditions in the Andes between 28–34°S. The floods were probably caused by major rainfall or dammed-lake outbursts clustered largely during wet pluvial periods in the otherwise moisture-limited central Andes and Atacama Desert, such as when the Intertropical Convergence Zone was shifted southward. These include Central Andean pluvial events (CAPE) I (17–14.5 ka) and II (12.5–9 ka), and the Neoglacial/Formative archeological period 2500 ka to near-present.